THE VAGUENESS OF THE NORM OF ENTRAPMENT IN DRUG OFFENSES BY LAW ENFORCEMENT OFFICERS IN THE FUTURE - Fachrizal Afandi; Annisa Azzahra Burhan; I Nyoman Nurjaya (CV. RADJA PUBLIKA, 2025)
Undercover buying and controlled delivery are investigative techniques regulated by Law Number 35 of 2009 concerning Narcotics. This provision does not regulate the limitations for investigators when carrying out this technique. In practice, this technique does not work effectively, resulting in the failure of the investigation. So this study discusses how the application of Undercover buying and controlled delivery current supervision and how the formulation of criminal law policies in dealing with cases of entrapment of narcotics crimes committed by law enforcement officers in the future. This study uses normative research. The research results show that First, there is a need for renewal of covert buying techniques and supervised delivery. This is because there are 3 (three) legal problems in its implementation, namely there are still informants who are involved in narcotics trafficking, closed access to public information regarding covert purchasing techniques and delivery under supervision by the National Narcotics Agency and the potential for fabrication of cases. Therefore, in the future it is necessary to have the right formulation to overcome this by implementing regulations and legal standards for investigating narcotics crimes.